A Life-Changing Experience: Memories of City of St. John's Volunteers - Hannon, Sarah; Barrett, Terra (2016)
A Life-Changing Experience: Memories of City of St. John's Volunteers. Booklet about City of St. John's volunteers' experience. Interviews and photographs completed during July and August 2016. Interview excerpts compiled, transcribed and edited by Sarah Hannon.